THE YOUTH'S EDUCATION AS AN ESSENTIAL FACTOR OF INCREASING THE EFFECTIVENESS OF EDUCATION (Academicia Globe: Inderscience Research, 2022)
In the article, mature generation should not be consumers, but the creators and devotees of our modernized society, one of the main purpose of pedagogues and thoughts on conducting training on the process of personal development with students are described.